Functional Assessment of Chronic Illness Therapy-Fatigue is a reliable and valid measure in patients with active ankylosing spondylitis - David Cella; William R. Lenderking; Peter Chongpinitchai; Andrew G. Bushmakin; Oluwaseyi Dina; Lisy Wang; Joseph C. Cappelleri; Victoria Navarro-Compán (SpringerOpen, 2022)
Plain English summary Ankylosing spondylitis (AS) is a disease that causes pain and stiffness in the spine. AS is a chronic disease. Most people with AS experience fatigue (a feeling of being very tired or exhausted). People with more severe AS tend to have more fatigue and a lower level of well-being. Because of this, fatigue is an important symptom to measure in studies of AS. The Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) is a questionnaire that measures fatigue. It has 13 questions that assess level of fatigue over a week's time. The FACIT-F has not been studied in depth in people with AS. Therefore, we analyzed results from two clinical trials. We found that FACIT-F was a reliable and valid way to measure fatigue in adults with AS. This makes it a suitable tool to use in AS clinical trials.